Plan de mejora de gestión del empleo local en una empresa minera - Guevara Leon, Andres Rauselli (2024)
The present research aims to analyze the current local employment process at Cia Minera Coimolache S.A. in order to improve the percentage of hiring unskilled and semi-skilled labor that is currently available, by presenting an improvement proposal for Cia Minera Coimolache S.A. This proposal takes into account that this program has a significant impact on the management of the operating company, the contractor companies in charge, and the community where the operation is carried out. The proposal focuses on diagnosing the phases of the process flow that have been developed at Cia Minera Coimolache since 2022, concentrating on three main components identified within the local employment process that are considered the most important: Recruitment, Selection, and Hiring.